Reimagining Masculinity: Analyzing the Representation of Men in Shambhala (Pursuits: A Journal of English Studies, 2025)
This research article examines the representation of men in a Nepali cinema Shambhala. It is a film which amalgamates Buddhist philosophy, spiritual pilgrimage, and interpersonal struggles in the village of Himalayas. Mostly commercial popular films replicate the stereotypical images of masculinity whereas Shamabhala presents a nuanced picturization that encounters orthodox gender norms. This study concentrates on answering these research questions: how are male characters in Shambhala depicted in terms of emotional, spiritual, and psychological depth, what cinematic techniques are used to convey masculinity in the film, and in what ways does Shambhala resist or support traditional notions of masculinity? To search answers to the mentioned questions the research attracts cinematic analysis and gender theory to scrutinize the character arcs, emotional depth, spiritual transformation, and the interpersonal roles men occupy within in the narrative. The research recognizes an alteration from the governing patriarchal masculinity to a more fluid and introspective identity, portraying men as emotionally complex and spiritually aware. This study provides the budding discourse on gender in South Asian Cinema and unlocks a discourse on unconventional masculinities in non-Western contexts.